Realizing Order in Socio-Cultural Life Through Multicultural Education in Skow Sae Village, Jayapura City, Papua - Akhmad Kadir (Formosa Journal of Science and Technology, 2023)
This study discusses the importance of multicultural education in creating an orderly socio-cultural life in Skow Sae Village. The research method used is descriptive qualitative. The results of this study indicate that the people of Skouw Sae Village have high social values ​​and a sense of solidarity and are still entrenched amidst the behaviors of everyday life. So far, there have never been any reports of problems escalating to the point of becoming conflicts between indigenous peoples and migrants. Nevertheless, it is important to continue to maintain and care for diversity through multicultural education. As a recommendation, efforts to maintain socio-cultural order can be carried out by applying the concept of "the three centers of education" introduced by Ki Hadjar Dewantara, including; the educational process at home, school, and society.